Precarious social inclusion: chronic homelessness and impaired decision-making capacity. Issue 1 (March 2014) - Clapton, Jayne; Chenoweth, Lesley; McAuliffe, Donna; Clements, Natalie; Perry, Carolyn
<x content-type="archive" xml:space="preserve">Abstract</x> This paper presents findings from an online survey of practitioners working in the homelessness sector in Australia, that explored practitioner perspectives of policy and service delivery to people with impaired decision-making capacity who experience chronic homelessness. This paper identifies from the research that unrealistic, inflexible and conditional policy, program and service responses from both the public and community sectors restrict positive outcomes for people with impaired decision-making capacity who are chronically homeless. These are significantly affected by sectoral silos whereby service types could not coordinate to facilitate adequate support. Supportive practices constructed of unconditional, flexible and wrap around support are needed along with "no exclusion" eligibility criteria for access to services. New approaches are needed in developing policy and delivering human services to people with impaired decision-making capacity that redress chronic homelessness, and enhance the prosperity of social inclusion for this vulnerable group of people.